PRAKTIK NIKAH SIRRI DAN IMPLIKASINYA TERHADAP PERLINDUNGAN EKONOMI BAGI PEREMPUAN DALAM PERSPEKTIF HUKUM ISLAM - Pawe, Nunung Indrawati; Arsyad, Yusri Muhammad; Abu Baedah, Said Syafuddin; Lawang, Hasanna; Raehana, Syarifa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the practice of unregistered marriage and its implications for women's economic protection in Maurole District, Ende Regency, from the perspective of Islamic law and positive law. This study uses a qualitative method with a sociological and normative juridical approach. Primary data were obtained through interviews with women engaged in unregistered marriages, religious leaders, village officials, and KUA employees, while secondary data were obtained from scientific literature and laws and regulations, particularly Law Number 16 of 2019 concerning Marriage. The results of the study indicate that unregistered marriages still occur due to economic factors, premarital pregnancy, cultural factors, and low public legal awareness regarding the importance of marriage registration. Religiously, unregistered marriages are considered valid because they fulfill the pillars and requirements of marriage, but from a state perspective, such marriages do not have perfect evidentiary power. As a result, women experience vulnerability in demanding rights to maintenance, division of joint property, and economic security after divorce. From an Islamic legal perspective, women's economic protection has been regulated through the obligation to provide maintenance, dowry, and the principle of justice in line with the maqashid al-syariah. Therefore, marriage registration is an important instrument to ensure legal certainty and protection for women.